Entire radial bounded solutions for Leray-Lions equations of (p, q)-type - Mennuni Federica; Mugnai Dimitri; Salvatore Addolorata (Advances in Nonlinear Analysis)
We prove the existence of entire, radial, and signed bounded solutions for a quasilinear elliptic equation in RN{{\mathbb{R}}}^{N} driven by a Leray-Lions operator of the (p, q)-type. For this, we need an extension of related results by Boccardo-Murat-Puel and a variational approach in intersections of Banach spaces introduced by Candela-Palmieri.